2002
DOI: 10.1017/s1355838202023099
|View full text |Cite
|
Sign up to set email alerts
|

Mutational analysis identifies two separable roles of the Saccharomyces cerevisiae splicing factor Prp18

Abstract: Prp18 functions in the second step of pre-mRNA splicing, joining the spliceosome just prior to the transesterification reaction that creates the mature mRNA. Prp18 interacts with Slu7, and the functions of the two proteins are intertwined. Using the X-ray structure of Prp18, we have designed mutants in Prp18 that imply that Prp18 has two distinct roles in splicing. Deletion mutations were used to delineate the surface of Prp18 that interacts with Slu7, and point mutations in Prp18 were used to define amino aci… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
6
0

Year Published

2003
2003
2018
2018

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(8 citation statements)
references
References 29 publications
2
6
0
Order By: Relevance
“…Conformational rearrangement, induced by the ATPase Prp16, primes the 5′-exon and 3′SS for the initiation of the second step splicing (35)(36)(37). With the help of the splicing factors Slu7, Cdc40 (Prp17 in S. cerevisiae), Prp18, and the ATPase Prp22, the Step II reaction is completed, forming the post-catalytic spliceosome (P complex) (38)(39)(40)(41)(42)(43)(44)(45). We speculate that the central components of the spliceosomal catalytic center -ISL of U6 snRNA, Helix I of the U2/U6 duplex, and Loop I of U5 snRNA -maintain a generally similar conformation in the B act , B*, C, and P complexes (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Conformational rearrangement, induced by the ATPase Prp16, primes the 5′-exon and 3′SS for the initiation of the second step splicing (35)(36)(37). With the help of the splicing factors Slu7, Cdc40 (Prp17 in S. cerevisiae), Prp18, and the ATPase Prp22, the Step II reaction is completed, forming the post-catalytic spliceosome (P complex) (38)(39)(40)(41)(42)(43)(44)(45). We speculate that the central components of the spliceosomal catalytic center -ISL of U6 snRNA, Helix I of the U2/U6 duplex, and Loop I of U5 snRNA -maintain a generally similar conformation in the B act , B*, C, and P complexes (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, genetic and mutagenesis studies have demonstrated that the carboxy-terminal domain interacts with the protein Slu7 at a weakly conserved face of the domain, and with the protein component of U5 snRNP through the highly conserved loop region linking helices D and E [34, 35]. PRP18 is thought to orient U5 snRNP in a manner that aligns an RNA loop of U5 snRNP with the exon junction; PRP18 thereby guides a specific RNA-RNA interaction through direct protein-protein interactions.…”
Section: Discussionmentioning
confidence: 99%
“…PRP18 is an evolutionarily conserved protein, with orthologs found in other plants, yeasts and metazoans ( Figure S1 and Figure S2 ). Prp18 proteins typically have five alpha-helices separated by four loops, with a highly conserved loop between the fourth and fifth helices ( Bacíková and Horowitz 2002 ; Annamalai 2011 ). The A334V mutation we identified in the prp18a-1 mutant is in this highly conserved loop region ( Figure 3 ).…”
Section: Resultsmentioning
confidence: 99%
“…PRP18 is not essential in budding yeast but cells lacking this protein grow slowly and are temperature sensitive ( Bacíková and Horowitz 2002 ). Whether PRP18a is essential in Arabidopsis is unclear.…”
Section: Discussionmentioning
confidence: 99%